Motivation and Second Language Pragmatics: A Regulatory Focus Perspective - Zhang, Yiran; Papi, Mostafa (Frontiers in Psychology, 2021)
This study investigates how learners’ chronic motivational characteristics, that is their regulatory focus (Higgins, 1997), can account for differences in L2 pragmatic production in general and across situations with different levels of power, social distance, and imposition. One-hundred-twenty-one L1-Mandarin learners of English as a second language completed a regulatory focus questionnaire and a discourse completion task focusing on two types of speech acts: request and opinion. Multiple regression results showed that learners’ promotion focus, concerned with advancement, growth, accomplishments, positively predicted their pragmatic production in general, and especially in situations where the learner is subject to a higher degree of imposition, has lower power and is socially distant from the interlocutor. On the other hand, the prevention focus, which is concerned with safety, security, and calmness, negatively predicted pragmatic production, especially in those situations. The findings provide support for the role of motivational dispositions in the level of learners’ L2 pragmatic competence. Theoretical and instructional implications are discussed.